STUDI KELAYAKAN USAHA SELIPAN RIYANTO DENGAN MENGGUNAKAN METODE NPV, IRR, PI, DAN PP - Jaya, Gigieh Henggar; Hidrotunnisa, Hidrotunnisa; Aldila, Livianinda Elza; Purbowati, Ike Sitoresmi Mulyo; Prabowo, Pandu Aji; Athallah, Fikri; Ramadhani, Siti Laila; Setiadi, Muhammad Restu (Program Studi Teknik Pertanian, Fakultas Pertanian, Universitas Jenderal Soedirman, 2024)
Small Rice mill or called “Selipan” in Indonesian, is a series of rice mill machines with various engine capacities, generally found in agricultural production centers. Rice mills require relatively large investment costs for producers in the production area. A feasibility study on the rice mill business at Selipan Riyanto is needed to be a reference for pioneering similar businesses. A business feasibility study is a comprehensive assessment to assess the success of a business. Rice mills are industrial facilities designed to convert paddy into milled rice. The milling process includes a series of operations, including rice cleaning, hulling, polishing, and packaging. This study aimed to evaluate financial feasibility of Selipan Riyanto based on NPV (Net Present Value), PI (Profitability Index), IRR (Internal Rate of Return), and PP (Payback Period). The study's results obtained a value, NPV (Net Present Value) of Rp. 266.613.794, PI (Profitability Index) of 2.54, IRR (Internal Rate of Return) of 59%, and PP (Payback Period) of 1.46 years.